Re-Thinking Time at the Interface of Physics and Philosophy : The Forgotten Present - von Müller, Albrecht; Filk, Thomas (On Thinking,, 2015)
The current volume of the Parmenides Series "On Thinking" addresses our deepest and most personal experience of the world, the experience of "the present," from a modern perspective combining physics and philosophy. Many prominent researchers have contributed articles to the volume, in which they present models and express their opinions on and, in some cases, also their skepticism about the subject and how it may be (or may not be) addressed, as well as which aspects they consider most relevant in this context. While Einstein might have once hoped that "the present" would find its place in the theory of general relativity, in a later discussion with Carnap he expressed his disappointment that he was never able to achieve this goal. This collection of articles provides a unique overview of different modern approaches, representing not only a valuable summary for experts, but also a nearly inexhaustible source of profound and novel ideas for those who are simply interested in this question.